Subaltern Urbanization: Indian Insights for Urban Theory. (11th June 2020) - Mukhopadhyay, Partha; Zérah, Marie‐Hélène; Denis, Eric
Abstract: The concept of subaltern urbanization is about vibrant smaller settlements—outside the metropolitan shadow—sustainably supporting a dispersed pattern of urbanization. We propose a theoretical framework which draws on an empirical research collective using both large statistical and land‐use data sets and detailed case studies in non‐metropolitan Indian geographies. Anchored in postcolonial urban studies, it looks beyond the logic of agglomeration and questions our understanding of settlement hierarchies and the location of social and economic innovation processes, opening up an alternative reading of urbanization that could be valuable for other regions. Local agency is core to this concept, transporting the arguments of the ordinary and the subaltern beyond large cities. Our findings, apart from emphasizing the agency of smaller settlements, highlight their multiple local and translocal flows, shaping an autonomous external engagement that could exist independently of relationships with large cities. Further, even though the rural and the urban seep into each other, they do so organically, unlike the process in planetary urbanization. Additionally, the rural‐urban dichotomy remains performative, in that governance regimes influence the urbanization process. Appreciation of these dynamics can provide insights towards a better understanding of the system of human settlements, which is our goal in advancing this framework.